CAPITAL STRUCTURE DETERMINANTS OF KSE LISTED AUTOMOBILE COMPANIES - Maryam Masnoon; Abiha Saeed (European Scientific Journal, ESJ, 2014)
This study aims to explore the various factors that determine the choice of financing sources for public limited companies in the automobile sector of Pakistan. The impact of firms’ profitability, liquidity, tangibility, size and earning variability on capital structure of KSE listed automobile companies is investigated. Panel data of ten out of sixteen companies for five years (2008-2012) is studied through regression analysis. It is found that capital structure has negative correlation with profitability, liquidity, size and tangibility, while it is positively correlated with earning variability. The association with profitability and liquidity is found to be statistically significant while that with size, tangibility and earning variability is reported as statistically insignificant.